Strength comparison of concrete with surface finishes and cement replacement by rebound hammer (RH) and compression machine - Rose Emmy Anak Kelbin (School of Environmental Engineering, University Malaysia Perlis, 2012)
The study of this paper is to compare the rebound hammer (RH) number with compression testing machine. The result of RH towards compressive strength of the concrete with surface finishes by tile and mortar placed on it also being study. Concrete with it cement was replaced by metakaolin(MK) and limestone about 50% also had been evaluated it strength by RH. 54 samples was prepared and tested. 27 samples tested during the 7 days and the other 27 was tested for 28 days strength by RH and compression testing machine. The result of the RH number and compression testing machine was compared. It was found that the RH number cannot be directly used as the compressive strength value. However a correlation can be made and obtained by an equation. Compressive strength of concrete can be obtained by the rebound value with an equation which used to correct the rebound hammer number and give the compressive strength value.